Numerical evaluations of a novel membrane element in simulations of reinforced concrete shear walls. (15th November 2019) - Chang, T.L.; Lee, C.-L.; Carr, A.J.; Dhakal, R.P.
Highlights: A simple method is proposed to obtain section resultant forces in 2D elements based on an interpolated stress field. A novel membrane element is investigated in simulations of reinforced concrete shear walls. Using 2D membrane elements with coarse mesh grids to model wall structures is possible. Abstract: Numerical simulation of reinforced concrete (RC) shear walls is a challenging task, due to the intricate underlying mechanics and the difficulty in balancing computational cost and accuracy. In the previous work, a general–purpose four–node quadrilateral drilling element named as GCMQ has been developed by the authors. This new element performs well with coarse meshes and provides engineers an option to efficiently simulate planar problems, such as shear walls subjected to in-plane loadings. Meanwhile, GCMQ can recover nonlinear distribution of stress field so that section resultant forces can be explicitly integrated. In this paper, GCMQ is validated via numerical simulations of several RC shear wall specimens with different reinforcement schemes and geometries. Compared to experimental results, numerical models show that GCMQ can accurately simulate in-plane response such as pushover backbones with a relatively low cost for both short and slender walls. With proper material models, it is also possible to recover other quantities such as damage distribution patterns. Since GCMQ is essentially a microscopic finite element, convergence is guaranteed, local response can also be obtained with mesh refinement. GCMQ could be used as a good tool for future modelling of shear walls and similar structures.